Costos operativos en la empresa Indumot S.A sucursal Babahoyo durante el periodo 2023. - Jacome Coello, Jordán Armando (2025)
The study established as its objective to examine the management of operating costs of the company Indumot S.A. Babahoyo branch by reviewing the accounting information for the period 2023, and the application of the methodology that refers to the use of descriptive and bibliographic methods was considered, carried out with the mixed research design and interview techniques through the respective guide to the person responsible for accounting, followed by observation and documentary review to carry out an internal control questionnaire and determine the accounting procedures, finally, the preparation of a comparative analysis using absolute and relative variations, which originated as findings the fixed costs are $ 182,559.35, the variable costs $ 1,007,592.70, the direct costs correspond to $ 1,00,592.70 and the indirect costs $ 206, 548.69. The comparative analysis revealed that there are accounts such as fuel, transportation, travel expenses, water, energy, electricity and telecommunications, notaries and registrars of commercial property, supplies and materials and other expenses that present a variation with a negative slope that ranges between -28% and -1% and refer to variable costs. In addition, fixed costs include insurance and reinsurance, management expenses, impairment expenses, administrative expenses such as salaries, wages, social security contributions, social benefits and compensation, taxes, contributions and others, in addition to financial expenses from loan interest whose real value is equal to the budgeted value. Therefore, it is pertinent to carry out a detailed analysis through internal control, which breaks down the origin of the deviation of variable costs through an exhaustive review of operating procedures.